2010
DOI: 10.1111/j.1528-1167.2010.02766.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B*1511 is a risk factor for carbamazepine‐induced Stevens‐Johnson syndrome and toxic epidermal necrolysis in Japanese patients

Abstract: Summary Stevens‐Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare but life‐threatening severe cutaneous adverse reactions. Recently, strong associations of HLA‐B*1502 with carbamazepine‐induced SJS/TEN have been found in Han Chinese patients. These associations have been confirmed in several Asian populations, excluding Japanese. SJS patients carrying HLA‐B*1508, HLA‐B*1511, or HLA‐B*1521, which are members of the HLA‐B75 type along with HLA‐B*1502, were detected in studies in India and Thai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(144 citation statements)
references
References 15 publications
10
129
1
4
Order By: Relevance
“…[20][21][22][23] Ueta et al reported a case-control study on the relationships between HLA class I and II genetic polymorphisms with severe ocular complications using 71 Japanese drug-unspecified SJS ⁄ TEN patients and 101 Japanese controls. No HLA-B*1502 carriers were detected in cases or controls.…”
Section: Allele Associations With Carbamazepine-induced Sjs ⁄ Ten In mentioning
confidence: 99%
“…[20][21][22][23] Ueta et al reported a case-control study on the relationships between HLA class I and II genetic polymorphisms with severe ocular complications using 71 Japanese drug-unspecified SJS ⁄ TEN patients and 101 Japanese controls. No HLA-B*1502 carriers were detected in cases or controls.…”
Section: Allele Associations With Carbamazepine-induced Sjs ⁄ Ten In mentioning
confidence: 99%
“…76 No association was found in Japanese, Korean or Caucasian individuals. HLA-A*3101 was recently associated with CBZ-HSR, CBZ-maculopapular exanthema and CBZ-SJS/TEN in North European Caucasians, 77 while HLA-B*1511 is associated with CBZ-SJS/TEN, 78 and HLA-A*3101 with CBZ-cutaneous ADRs in Japanese. 79 HLA-B*1502 was associated with CBZ-induced SJS/TEN, but not with CBZ-induced mild maculopapular eruptions in central China.…”
Section: Discussionmentioning
confidence: 99%
“…Pada dua penelitian berbeda di populasi Jepang HLA-A*31:01 (5 dari 6 pasien; 83,3%) dan HLA-B*15:11 (4 dari 14 pasien; 28,6%) menunjukkan hubungan dengan timbulnya SSJ-NET setelah mengkonsumsi karbamazepin. 19,20 Hal tersebut tidak berbeda jauh dengan hasil penelitian pada populasi Korea. Penderita SSJ-NET yang dipicu pemakaian karbamazepin pada populasi Korea diketahui memiliki HLA-A*31:01 dan HLA-B*15:11 dengan frekuensi yang sama (3 dari 7 pasien; 42,9%).…”
Section: Prevalensi Ssj-net Disebabkan Karbamazepinunclassified